Design and optimization of a compact quasi-isochronous 180-deg transport arc with suppressed CSR-induced emittance growth - Zhang, Chengyi; Jiao, Yi (Frontiers in Physics, 2023)
Preserving the beam quality of a high-brightness electron beam is a noteworthy issue when delivering the electron bunch through a beam transfer line. In a beam transfer line with a large deflection angle, e.g., a 180-deg transport arc comprised of a large amount of dipoles, emission of coherent synchrotron radiation (CSR) can lead to transverse emittance dilution. In addition, the longitudinal dispersion may cause undesirable bunch length variation. Both effects can degrade beam quality. Nevertheless, design and optimization of a 180-deg transport arc that can be well applied to practical applications is a challenging problem, considering the practical nonlinear effects of a real lattice and the contributions of transient CSR at the dipole edges and CSR in the subsequent drifts. In this study, we present the design and optimization of a compact 180-deg transport arc comprised of multi-triple-bend achromat (TBA) cells, aiming at suppressing the CSR-induced emittance growth and avoiding bunch length variation simultaneously. The TBA cells and optics along the arc are adjusted to suppress the CSR-induced emittance growth and bunch length variation cell by cell, after which a multi-objective optimization of the arc is conducted. Practical considerations including lattice nonlinear effects and a full one-dimensional CSR model (including transient CSR and CSR in drifts) are taken into account.